Law's picture books : the Yale Law Library collection - Widener, Michael; Widener, Michael; Weiner, Mark Stuart; Weiner, Mark Stuart (Talbot Publishing, 2017)
Collecting Yale Law Library's picture books / Michael Widener -- Reflections on an exhibition / Mark S. Weiner -- Ars Memoria in early law : looking beneath the picture / Jolande Goldberg -- Law's picture books and the history of book illustration / Erin C. Blake -- Law's picture books: The Yale Law Library collection. Symbolizing the law -- Depicting the law -- Diagramming the law -- Calculating the law -- Staging the law -- Inflicting the law -- Arguing the law -- Teaching the law -- Laughing-and crying-at the law -- Beautifying the law